Detectability of Malignant Lesions by Whole-Body Magnetic Resonance Imaging Using Whole-Body Integrated Positron Emission Tomography/Magnetic Resonance Imaging. Issue 4 (July 2019) - Ishii, Shiro; Miyajima, Masayuki; Suenaga, Hiroki; Sugawara, Shigeyasu; Nemoto, Ayaka; Ukon, Naoyuki; Nambu, Takeyuki; Kubo, Hitoshi; Oriuchi, Noboru; Ito, Hiroshi
Abstract : Purpose: To assess the diagnostic ability of whole-body magnetic resonance imaging (MRI) using integrated positron emission tomography/MRI(PET/MRI). Methods: Axial T2-weighted image (T2WI), diffusion-weighted imaging (DWI), coronal T1-weighted image (T1WI), axial volumetric interpolated breath-hold examination in the lung field, and 2-[fluorine-18]-fluoro-2-deoxy-D-glucose (FDG–PET) were evaluated in combination with T2WI alone, T2WI + DWI, T2WI + DWI + T1WI, T2WI + DWI + T1WI + volumetric interpolated breath-hold examination (all MRI images), and all MRI + FDG-PET. Results: A total of 370 lesions were observed in 90 (62.5%) of the 144 patients. The lesion-based sensitivities were 62%, 74%, 74%, 76%, and 94%, and the patient-based sensitivities were 70%, 77%, 77%, 77%, and 81% using T2WI, T2WI + DWI, T2WI + DWI + T1WI, all MRI, and all MRI + FDG-PET, respectively. There were significant differences in the lesion-based sensitivity between T2WI and other sequence combinations and between all MRI and all MRI + FDG-PET. No significant differences were observed between any combinations among the patient-based sensitivities. Conclusion: The sensitivity of whole-body MRI was lower when lesion based, but almost equivalent when patient based compared with PET/MRI.